Anti-Oxidative and Anti-Inflammatory Properties of Xanthorrhizol in Airway Inflammation - Liao, Wupeng; Wong, Wai Shiu Fred (Journal of Basic and Applied Pharmacology, 2022)
Inflammation and oxidative damage contribute to the pathogenesis of chronic pulmonary diseases. Xanthorrhizol (XNT), a natural sesquiterpenoid from Curcuma xanthorrhiza, has been shown to have anti-microbial, anti-oxidative and anti-inflammatory properties. The present study evaluated the anti-oxidative and anti-inflammatory activities of XNT in various cell-free and cell culture models. XNT was found to possess a moderate free radical-scavenging capability using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) cell-free assay, whose potency is lower than, but efficacy is comparable to the FDA-approved antioxidant agent trolox. In aeroallergen house dust mite (HDM)- and lipopolysaccharide (LPS)-stimulated Raw 264.7 macrophage cell line, XNT down-regulated both mRNA expression and protein production of proinflammatory cytokines and chemokines including TNF-α, IL-1β, IL-6, GM-CSF, etc. In addition, XNT was able to directly activate multiple antioxidant genes such as Hmox1 (Hemoxygenase-1), Nqo1 (NADPH quinone oxidoreductase-1), Gsr (glutathione reductase), and Gpx1 (glutathione peroxidase 1) in Raw 264.7 cell line. Furthermore, XNT suppressed corticosteroid-resistant cytokine IL-27 and IL-6 production in mouse primary alveolar macrophages upon combined LPS/IFN-γ stimulation, which implicates a severe subtype of asthma. Particularly, by combining cell surface markers with intracellular cytokine staining strategy, it was shown, for the first time that XNT decreased Th2/Th17 cytokine IL-5-, IL-13- and IL-17-expressing CD4 T cell frequency in single cell suspension isolated from HDM- and aspergillus fumigatus (AF)-exposed mouse lungs. Taken together, our findings reveal novel anti-oxidative and anti-inflammatory properties of XNT and implicate a new potential treatment to chronic pulmonary diseases.